2018
DOI: 10.32737/2221-8688-2018-3-283-306
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalysts for Water Electrolysis

Abstract: The review paper accumulates the latest information on the analysis of catalyst synthesis for the electrolysis of water in alkaline and partially in acidic media. Literature data on the production of electro-catalysts based on noble, refractory, transition and pure metals, as well as metals doped with molybdenum, phosphorus, and other elements, are presented. Given the different methods of synthesis of electro-catalyst, the advantage of the electrochemical method is emphasized as easy, accessible method enabli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 114 publications
(172 reference statements)
0
11
0
Order By: Relevance
“…The presence of oxygen in the sediments is explained by the fact that nickel deposits together with molybdenum oxides [31,32]. In [16], it was suggested that the deposition of the Ni-Mo alloy usually occurs through the formation of an intermediate complex of molybdenum and nickel, where the divalent nickel ion plays catalyst role. A porous film of a mixture of molybdenum and nickel oxides was found on the cathode surface.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of oxygen in the sediments is explained by the fact that nickel deposits together with molybdenum oxides [31,32]. In [16], it was suggested that the deposition of the Ni-Mo alloy usually occurs through the formation of an intermediate complex of molybdenum and nickel, where the divalent nickel ion plays catalyst role. A porous film of a mixture of molybdenum and nickel oxides was found on the cathode surface.…”
Section: Discussion Of the Resultsmentioning
confidence: 99%
“…Ni-Mo alloys are considered highly active catalysts for the hydrogen evolution reaction in alkaline electrolytes. The study of the kinetics and mechanism of HER on electrodeposited Ni-Mo alloys has been carried out by many scientists [11][12][13][14][15][16][17]. In works [18,19], dedicated to the electrodeposition of Ni-Mo alloys, the mechanism of induced codeposition is discussed.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, due to the width of the band gap (1.7 eV), it can be used as a part for solar cells [10] and photoelectrode materials for the production of hydrogen [11][12][13]. Recent studies have shown that MoS 2 nanoparticles are promising and inexpensive alternatives to platinum using for electrochemical and photochemical hydrogen production from water [14][15][16][17].…”
mentioning
confidence: 99%